3a-6=6a+12

Simple and best practice solution for 3a-6=6a+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3a-6=6a+12 equation:


Simplifying
3a + -6 = 6a + 12

Reorder the terms:
-6 + 3a = 6a + 12

Reorder the terms:
-6 + 3a = 12 + 6a

Solving
-6 + 3a = 12 + 6a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-6a' to each side of the equation.
-6 + 3a + -6a = 12 + 6a + -6a

Combine like terms: 3a + -6a = -3a
-6 + -3a = 12 + 6a + -6a

Combine like terms: 6a + -6a = 0
-6 + -3a = 12 + 0
-6 + -3a = 12

Add '6' to each side of the equation.
-6 + 6 + -3a = 12 + 6

Combine like terms: -6 + 6 = 0
0 + -3a = 12 + 6
-3a = 12 + 6

Combine like terms: 12 + 6 = 18
-3a = 18

Divide each side by '-3'.
a = -6

Simplifying
a = -6

See similar equations:

| 3a-4=6a+12 | | 3a-4=12a+12 | | 3a-12=12a+12 | | 4a-12=12a+12 | | 4a-12=15a+12 | | 4a-12=5a+12 | | 4a-12=10a+12 | | 4a-6=10a+12 | | 4a-6=10a+8 | | 49m^2-16=0 | | jk^2-9j=0 | | 4x-3(x-2)=2(x-1) | | 8j^2-32=0 | | 3h^2-12=0 | | 5x-2=10x-8 | | 2x*6= | | (4+x)(x-4)= | | x^3+3x^2-9x-8=0 | | y=x^3+3x^2+9x-10 | | 20x^2*5x*2=0 | | 6-x=4+x | | 6a+4a= | | ln(2x-9)=0 | | 9.6-y=7.2+2y | | 4p^2=-13p-3 | | 7=p+2q | | 2v-7=19 | | 100+34= | | 5x^2-8x=-5x+8 | | (3x^2+5x+7)-(2x^2-3x+10)= | | t^2-t=3t+21 | | w^2+7w=18 |

Equations solver categories